PEMBERDAYAAN UMKM PADA MASA PANDEMI COVID-19 DI KOTA PEKANBARU - Fahrial Fahrial; Andrew Shandy Utama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
One of the goals of the establishment of Indonesia as a country is to improve the welfare of the people. The Covid-19 pandemic that has hit Indonesia since March 2020 has greatly affected the condition of the national economy, including in Pekanbaru City. The method used in this research is sociological law research. The strategy that can be applied by MSME actors in Pekanbaru City to survive during the Covid-19 pandemic is to make creative innovations that do not violate government policies. Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises stipulates that the government is obliged to empower MSMEs in order to maintain national economic stability. Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises stipulates that the forms of empowering MSMEs that must be carried out by the government include funding assistance, improving facilities and infrastructure, information on business opportunities, partnership programs, facilitating business licensing, providing business opportunities, conducting trade promotion activities, as well as institutional support.Keywords: MSMEs, Empowerment, Covid-19 Pandemic